Who discovered what when / David Ellyard. - Ellyard, David, 1942- (Reed New Holland, 2005)
An absorbing introduction to the growth of scientific knowledge over the last 500 years. It sets important discoveries in a context of time and place, and introduces the reader to the people who brought them to life.